Malaria Prevention Strategies in Kalimantan, Indonesia: A Secondary Analysis of 2018 Basic Health Research Data - Muhammad Rasyid Ridha; Dicky Andiarsa; Ihya Hazairin Noor; Erni Wiliyani; Tri Ramadhani; Ririh Yudhastuti (Nurse Media: Journal of Nursing, 2024)
Background:  Kalimantan remains malaria-endemic, particularly in rural areas, where prevention efforts face challenges such as insecticide resistance and limited healthcare access. Despite available measures like insecticide-treated nets, gaps in understanding individual and household prevention practices persist, especially in relation to demographics and effectiveness in reducing malaria transmission.